Sargent' s pseudo-keynesianism (1994)
The assumptions of the Sargent model guarantee stabili ty wi thin avery limited framework which omits basic theoretical considerations.The article tries to show that (1) aggregate logic of the model notonly denies the essence of Keynesian macroeconomic analysis, but alsodoes not solve the old problem of how to pass from the relationshipbetween individuals to global interactions between forces in theeconomy; and (2) Sargent's conclusions on economic policy arepresented as universally valid, but are derived from highly restrictiveassumptions and conditions. The author ignores other situationswhich are equally likely to occur, but would give mathematicalresults and policy recommendations totally different from those ofthe author.